PENGGUNAAN TEKNOLOGI ANDROID DALAM PENERJEMAHAN BAHASA SUMBER KE BAHASA SASARAN (Studi Kasus Siswa SMK Putra Gununghalu Era Digital) - Sadiyah; Deasy Nurmaulidah; Nurlaeni; Wasliman, Iim; Sauri, R. Supyan; Gaffar, M. Andriana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study is to identify the extent of the use of Android technology in translating English texts. The researcher employed a case study approach in this research. A case study is one of the approaches within the qualitative research paradigm. The aim is to describe and examine the effectiveness of using Android technology in translating words from the source language into the target language, as well as the factors that motivate students to use it. Three methods were used to collect the research data, namely classroom observation, interviews, and questionnaires. The research sample consisted of second-grade students of Putra Gununghalu Vocational School, totaling 100 students in the 2025–2026 academic year. The results of the study show that students rarely bring English dictionaries when attending translation classes. One of the reasons is the availability of Android technology, which is easy to use, convenient, practical, and easy to carry in a pocket. When students have difficulty finding the meaning of a word, they simply type the word on their mobile phones by accessing Google Translate. Students also trust the accuracy of the meanings obtained through mobile access. Therefore, they consistently use it whenever they encounter difficulties in finding word meanings.The translation method used by students is still word-for-word translation. This is also related to language structure. In other words, students tend to follow the structure of the source language.